\(x=\sqrt3+\cfrac{1}{\sqrt3}\), \(y=\sqrt3-\cfrac{1}{\sqrt3}\) হলে \(\cfrac{x^2}{y}+\cfrac{y^2}{x}\) - এর মান নির্ণয় করো ।
Madhyamik 2009
\(x+y=\sqrt3+\cfrac{1}{\sqrt3}+\sqrt3-\cfrac{1}{\sqrt3}=2\sqrt3\)
\(xy=\left(\sqrt3+\cfrac{1}{\sqrt3}\right)\left(\sqrt3-\cfrac{1}{\sqrt3}\right)\)
\(=\left(\sqrt3\right)^2-\left(\cfrac{1}{\sqrt3}\right)^2=3-\cfrac{1}{3}\)
\(=\cfrac{9-1}{3}=\cfrac{8}{3}\)
\(\cfrac{x^2}{y}+\cfrac{y^2}{x}\)
\(=\cfrac{x^3+y^3}{xy}\)
\(=\cfrac{(x+y)^3-3xy(x+y)}{xy}\)
\(=\cfrac{(2\sqrt3)^3-3\times \cfrac{8}{3}\times 2\sqrt3}{\cfrac{8}{3}}\)
\(=\cfrac{24\sqrt3-16\sqrt3}{\cfrac{8}{3}}\)
\(=8\sqrt3\times\cfrac{3}{8}\)
\(=3\sqrt3\) (Answer)